Pemahaman Masa Iddah Setelah Perceraian Pada Masyarakat Muslim Indonesia - Dzulfatah Yasin (Prodi Ahwal Syakhsiyah, Fakultas Syariah, Institut PTIQ Jakarta, 2023)
This research examines the scholarly debates surrounding the iddah period in the context of Islamic law in Indonesia. The focus of this research is on a comparative study of the diverse understandings of iddah among various schools of thought and scholars in Indonesia. The research approach used is document analysis, utilizing various primary sources such as classical Islamic texts and scholars' fatwas. A comparative approach is employed to compare the views of scholars from different schools of thought, such as the Shafi'i, Hanafi, Maliki, and Hambali schools. The results show that there are significant differences of opinion among scholars regarding various aspects of the iddah period, including its duration, the ruling for women who are pregnant when widowed, and the regulation of iddah for divorced women. These debates reflect the diversity of views and interpretations among Indonesian scholars, influenced by factors such as cultural context, local traditions, and interpretations of religious texts. The implications of this research highlight the importance of understanding local contexts in interpreting Islamic law, as well as the need for dialogue among scholars to achieve a more comprehensive and inclusive understanding of Islamic legal issues. Recommendations for further research include conducting more in-depth studies on Indonesian scholars' thoughts on the iddah period and comparative studies with other countries to enrich the discourse of Islamic scholarship in Indonesia and internationally.